(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Self-compacted concrete (SCC) is cast within the formwork without compaction and it fulfills the formwork because of its personal weight. SCC is taken into consideration to have many benefits in contrast with traditional concrete like improved construction, economic and time saving, quicker construction activity etc. SCC is produced with the same materials of ordinary concrete. Cementatious materials are adopted to replace the cement content in SCC so that waste materials (bauxite) from industries and agricultural products can be used. Further improvement in the performance of SCC is done by using different types of fibers to produce fiber reinforced SCC and to diffuse the crack propagation which improves mechanical properties. The foremost goal of this paper is to collect the literature to recognize the use of cement alternative materials (bauxite) and fibers for reducing the environmental hazards. This paper discusses the environmental implications due to the technology of diverse solid wastes, and highlights their recycling potentials and viable use for generating productive materials.